Clinical characteristics and mortality in all Czech patients after pacemaker implantation in the last decade - Táborský, Miloš; Skála, Tomáš; Dušek, Ladislav; Kautzner, Josef; Aiglová, Renata; Fedorco, Marián; Jarkovský, Jiří; Benešová, Klára; Májková, Petra (Frontiers in Cardiovascular Medicine, 2023)
Background and Aims Analysis of mortality from the national health registries and data from a specific central registry dealing with the implantation of pacemakers (REPACE) in Czech patients. Methods and results Retrospective observational analysis of pacemakers’ implantation in all Czech patients (n=82,791; 47,070 (56.9%) men, 75.9 ± 10.4 years old) between 2010 and 2021. Almost 114,000 pacemakers were implanted between 2010 and 2021, of which 27.9% were single-chamber, 67.4% were dual-chamber and 4.6% were biventricular. The annual number of implantations has been steadily increasing with a 6% annual decline in 2020 with increased mortality and reductions in care provided, likely related to COVID-19. The observed 5-year relative survival was 88.6% (overall survival 60.6%) and the 10-year relative survival was 75.9% (overall survival 32.7%). Causes of death vary according to the age of the patient. The highest difference in the reported numbers in the REPACE Registry did not exceed 2 % in comparison with the National Register of Reimbursed Health Services. Conclusion This study followed all Czech patients with pacemaker’s implantation in between 2010 and 2021. The annual number of implantations has been steadily increasing. Patients with implanted pacemakers had a significantly higher mortality than the average population. Number of patients in the registry corresponded almost perfectly with the National Register of Reimbursed Health Services.